2012
DOI: 10.1161/circep.111.966580
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cx43 Expression Triggers Increased Fibrosis Due to Enhanced Fibroblast Activity

Abstract: Background-Arrhythmogenic ventricular remodeling is hallmarked by both reduced gap junction expression and increased collagen deposition. We hypothesized that reduced connexin43 (Cx43) expression is responsible for enhanced fibrosis in the remodeled heart, resulting in an arrhythmogenic substrate. Therefore, we investigated the effect of normal or reduced Cx43 expression on the formation of fibrosis in a physiological (aging) and pathophysiological (transverse aortic constriction [TAC]) mouse model. Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 38 publications
2
72
1
Order By: Relevance
“…Moreover, it is conceivable that the down regulation of CX43 in cells expressing D243Gfs*4 may be involved also in the fibrosis found in the index patient. Interestingly, it has been demonstrated that the reduced Cx43 expression in a CX43 transgenic mouse model, triggers increased myocardial fibrosis due to enhanced activity of non-excitable cardiac fibroblasts [37]. Of note, this work suggests that early normalization of Cx43 expression might prevent fibrosis formation and reduce the susceptibility to fatal arrhythmia, underlying the clinical importance in identifying CX43 as the player involved in the cardiomyopathy pathogenesis.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, it is conceivable that the down regulation of CX43 in cells expressing D243Gfs*4 may be involved also in the fibrosis found in the index patient. Interestingly, it has been demonstrated that the reduced Cx43 expression in a CX43 transgenic mouse model, triggers increased myocardial fibrosis due to enhanced activity of non-excitable cardiac fibroblasts [37]. Of note, this work suggests that early normalization of Cx43 expression might prevent fibrosis formation and reduce the susceptibility to fatal arrhythmia, underlying the clinical importance in identifying CX43 as the player involved in the cardiomyopathy pathogenesis.…”
Section: Discussionmentioning
confidence: 81%
“…102 In these studies, CVs and activation delays were estimated using high-resolution extracellular epicardial mapping; axial CV was unchanged, whereas significant rate-dependent transverse activation delays were seen. The probability of inducing VT and fibrillation in these hearts was increased by the presence of patchy fibrosis.…”
Section: Fibrosis Hf and Vtmentioning
confidence: 99%
“…The probability of inducing VT and fibrillation in these hearts was increased by the presence of patchy fibrosis. 96,102 Furthermore, inhibition of the renin-angiotensin-aldosterone system in aging mice limited age-related fibrosis, decreased the extent of electric anisotropy, and lowered arrhythmogeneity. 103 The preservation of axial CV in HF suggests that gap junction remodeling and fibroblast/myofibroblast infiltration have relatively little impact on this parameter.…”
Section: Fibrosis Hf and Vtmentioning
confidence: 99%
“…These myocardial alterations compromise cell-to-cell contacts and Cx43 channels mediated communication in diseased or aged heart and promote the occurrence of malignant arrhythmias (Tribulova et al 2008;Jansen et al 2012;Radosinska et al 2013). Fibrotic remodelling is attributed to miR-21 that is specifically enriched in cardiac fibroblasts promoting their activation and induction of extracellular signal-regulated signalling pathway (Thum et al 2008).…”
Section: Introductionmentioning
confidence: 99%